3D Printing of Viscoelastic Suspensions via Digital Light Synthesis for Tough Nanoparticle–Elastomer Composites. Issue 25 (17th May 2020) - Wang, Kaiyang; Pan, Wenyang; Liu, Zheng; Wallin, Thomas J.; van Dover, Geoffrey; Li, Shuo; Giannelis, Emmanuel P.; Menguc, Yigit; Shepherd, Robert F.
Abstract: The rheological parameters required to print viscoelastic nanoparticle suspensions toward tough elastomers via Digital Light Synthesis (DLS) (an inverted projection stereolithography system) are reported. With a model material of functionalized silica nanoparticles suspended in a poly(dimethylsiloxane) matrix, the rheological‐parameters‐guided DLS can print structures seven times tougher than those formed from the neat polymers. The large yield stress and high viscosity associated with these high concentration nanoparticle suspensions, however, may prevent pressure‐driven flow, a mechanism essential to stereolithography‐based printing. Thus, to better predict and evaluate the printability of high concentration nanoparticle suspensions, the boundary of rheological properties compatible with DLS is defined using a non‐dimensional Peclet number ( Pe ). Based on the proposed analysis of rheological parameters, the border of printability at standard temperature and pressure (STP) is established by resin with a silica nanoparticle mass fraction (ϕsilica ) of 0.15. Above this concentration, nanoparticle suspensions have Pe > 1 and are not printable. Beyond STP, the printability can be further extended to ϕsilica = 0.20 via a heating module with lower shear rate to reduce the Pe < 1. The printed rubber possesses even higher toughness ( Γ ≈ 155 kJ m −3 ), which is 40% higher over that of ϕsilica = 0.15. Abstract : The pressure‐driven flow in continuous Digital Light Synthesis is analyzed through the dimensionless Peclet number. This mechanism enables the 3D printing of resins with yield stress (≈10 Pa) and high viscosity (≈200 Pa s), which are the typical rheological features of suspensions with high nanoparticle content. This concept is applied to fabricate silicone–silica nanocomposites with enhanced toughness.